A case of laparoscopic appendectomy for appendiceal bleeding - Takuya Nakashima; Bun Sano; Aiko Ikawa; Kakeru Tawada; Tomohito Shinoda; Shinya Ohno; Reo Tachikawa (Surgical Case Reports)
Abstract Background Appendiceal bleeding is very rare, accounting for about 0.4% of all lower gastrointestinal bleeding. We present a case of laparoscopic appendectomy in a patient with a diagnosis of appendiceal bleeding. Case presentation A 71-year-old man came to our hospital with a complaint of bloody stools. He had progressive anemia and persistent fresh bloody stools, so he underwent lower gastrointestinal endoscopy. Active bleeding was confirmed from the orifice of the appendix, but the bleeding could not be stopped even with clips, so an emergency laparoscopic appendectomy was performed. His postoperative course was good, and he was discharged on the third postoperative day. Although the pathology results did not allow identification of the source of the bleeding, an appendiceal diverticulum was observed, and appendiceal diverticular bleeding was suspected. Conclusion Appendiceal bleeding is often difficult to stop endoscopically, so appendectomy should be performed as soon as possible.